Towards a Unified and Adaptive Smart Home System: Deep Learning and iot Integration - Xu, Denghan (Transactions on Computer Science and Intelligent Systems Research, 2025)
With the wide application of IoT technology in daily life, the smart home industry has achieved rapid development in recent years. However, due to the different communication methods and fragmented functions between different smart home devices, this makes users face higher complexity in management and use. The goal of the smart home management and control platform is to integrate the data monitoring and control functions of multiple devices in a heterogeneous network environment to provide one-stop home services. However, in the face of problems such as coordination between devices, numerous environmental parameters and difficult to accurately identify user needs, how to build a unified management and control system that is imperceptible, accurate and intelligent has become a core problem to be solved in the process of smart home platformization. The system not only can be used for normal residential home user, but also can be used for hotel and other subsystems. The system realizes the remote control of appliances combine locality control the results show that the system hardware is simple, lower cost, reliability and easy to expand.